Quizizz Media to Improve Students' Motivation and Storytelling Ability at SD Muhammadiyah Purworejo - Puspa Dewi; Arum Ratnaningsih (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2023)
This research aims to determine the increase in students' motivation in participating in learning and language skills, especially telling stories using Quizizz media at Muhammadiyah Elementary School, Purworejo. This type of research uses mixed research methods, namely using qualitative methods to measure motivation and using quantitative methods to measure the increase in students‘ storytelling abilities. The subjects in this research were students at SD Muhammadiyah Purworejo. Data collection uses interview, observation, and test related to the Quizizz media learning process. Data analysis techniques use descriptive statistics and inferential statistics. This media improved the students‘ storytelling ability and their motivation in learning. It received a positive response for its use in the learning process so it is suitable as a solution to problems that arise for students. They become more enthusiastic and enthusiastic, so they can eliminate feelings of boredom and laziness while learning from home because it provides a feeling of fun, comfort, and humor in learning. So that their intellectual intelligence can develop well.